'We're out, so wtf do we do now?': Brexit and rural identity in the era of online agricultural communities. Issue 2 (22nd February 2022) - Jones‐Garcia, Eliot; Touboulic, Anne
Abstract: This article explores online interactions between members of the UK farming community in the context of Brexit, a moment of great friction within British agriculture. A 'netnography' was conducted of thefarmingforum.co.uk, a British‐based discussion group with a large membership, covering a range of aspects from farming practices to trade and relationships. Findings reveal how the online space challenges and connects notions of rural space and place. A displaced identity, unmoored from traditional farming attributes such as land and locality, becomes both a driving force for participation and a tool for political control. The article sheds light on the under‐appreciated political power of such online groups enabled through under‐researched digital technologies. The farmer‐owned forum represents the 'other voice' within corporate‐led agricultural innovation; however, the onset of Brexit became a catalyst for extreme politics, facilitating a populist swing towards the Leave campaign and revealing a visceral distrust for institutions.